2011
DOI: 10.1007/s00384-011-1252-2
|View full text |Cite
|
Sign up to set email alerts
|

Focused preoperative patient stoma education, prior to ileostomy formation after anterior resection, contributes to a reduction in delayed discharge within the enhanced recovery programme

Abstract: Delayed discharge secondary to independent stoma management can be significantly reduced with preoperative stoma management teaching as part of an enhanced recovery programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 22 publications
7
54
0
1
Order By: Relevance
“…This rate may be lower than those of previously published reports as a result of differences in patient population as well as extensive patient education regarding hydration and titration of anti-diarrheal medications, aggressive surveillance by nursing staff, close follow-up, and servicing a well-educated population. Several prospective studies have successfully employed educational interventions and “ileostomy pathways,” resulting in decreased hospital LOS, reduced stoma-related complications, and improved quality of life [3133]. However, 2 systematic reviews on this topic demonstrated conflicting results: one concluded that structured patient education programs reduced hospital costs and improved quality of life [34], while the other found the use of educational interventions for new ostomates have limited evidence for improvement in clinical outcomes [35].…”
Section: Discussionmentioning
confidence: 99%
“…This rate may be lower than those of previously published reports as a result of differences in patient population as well as extensive patient education regarding hydration and titration of anti-diarrheal medications, aggressive surveillance by nursing staff, close follow-up, and servicing a well-educated population. Several prospective studies have successfully employed educational interventions and “ileostomy pathways,” resulting in decreased hospital LOS, reduced stoma-related complications, and improved quality of life [3133]. However, 2 systematic reviews on this topic demonstrated conflicting results: one concluded that structured patient education programs reduced hospital costs and improved quality of life [34], while the other found the use of educational interventions for new ostomates have limited evidence for improvement in clinical outcomes [35].…”
Section: Discussionmentioning
confidence: 99%
“…As a part of enhanced recovery programs, peri-operative stoma teaching reduces postoperative length of stay and complications, but has not been associated with an overall reduction in readmissions 8, 9 . Nagle and colleagues reported that an “ileostomy pathway” focused on patient self-management eliminated readmissions for dehydration, but did not significantly change readmission rates overall 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In new patient groups entering an ERAS program, nutrition recommendations should be properly integrated into the guidelines to achieve an optimal preoperative status and to reduce perioperative complications, especially in malnourished patients. An important predictor for the success of an ERAS program is personalized counseling [112,113]. Patients undergoing esophagectomy incur significant psychological stress [114], and their individual disease perceptions are a larger determinant of psychological outcome than coping strategies [115], yet surgeons often fail to appreciate or address them [116].…”
Section: Enhanced Recovery After Surgery Programmentioning
confidence: 99%